2013
DOI: 10.1080/14786419.2012.688044
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial activities of aporphinoids and other alkaloids from the bark ofAnnona salzmanniiA. DC. (Annonaceae)

Abstract: The antioxidant capacity by oxygen radical absorbance capacity (ORAC)-FL method and antimicrobial activity using the broth microdilution method of aporphinoids (liriodenine 1, anonaine 2 and asimilobine 3) and other alkaloids (reticuline 4 and cleistopholine 5) isolated from the bark of Annona salzmannii A. DC. (Annonaceae) were evaluated. For antioxidant activity, the most active alkaloid was asimilobine with ORAC value of 2.09 relative trolox equivalents. For antimicrobial activity, some alkaloids showed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 7 publications
1
42
0
Order By: Relevance
“…Among the tested compounds, 170 exhibited the best activity with MIC values of 0.2 and 0.3 μM against E. coli and E. luteus , respectively, while 167 and 169 showed the weakest activity with MIC values of 2.6 μM against E. coli and 10.5 μM against E. luteus . The benzo[g]quinoline‐5,10‐dione cleistopholine ( 171 ) (Figure ) from the fruiting tree Annona salzmannii showed significant antibacterial activity (MIC 250 μg/mL) against S. epidermidis , E. faecalis , and Candida dubliniensis …”
Section: Biological Activities Of Quinoline and Quinazoline Alkaloidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the tested compounds, 170 exhibited the best activity with MIC values of 0.2 and 0.3 μM against E. coli and E. luteus , respectively, while 167 and 169 showed the weakest activity with MIC values of 2.6 μM against E. coli and 10.5 μM against E. luteus . The benzo[g]quinoline‐5,10‐dione cleistopholine ( 171 ) (Figure ) from the fruiting tree Annona salzmannii showed significant antibacterial activity (MIC 250 μg/mL) against S. epidermidis , E. faecalis , and Candida dubliniensis …”
Section: Biological Activities Of Quinoline and Quinazoline Alkaloidsmentioning
confidence: 99%
“…The nitrogen oxide group was essential for the activity, as well as the length of the alkyl chain. The oxygen radical absorbance capacity (ORAC) value of cleistopholine, a quinoline alkaloid found in A. salzmannii , was 0.25 relative trolox equivalents …”
Section: Biological Activities Of Quinoline and Quinazoline Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gayle et al, [34] and Hadden et al, [35] had also reported that T. erecta flowers are rich in flavonoids, alkaloids and glycosides. Plants rich in phytoconstituents like alkaloids, flavonoids, tannins, terpenoids and steroids have antibacterial properties [36,37]. In addition, secondary metabolites such as tannins and other compounds of phenolic nature are also classified as active antimicrobial compounds [38].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Therefore, it may be concluded that antioxidative belongings resulted are due to qualitative and quantitative presence of phenolic groups in their structures. The alkaloid asimilobine isolated from bark of Annona salzmannii has showed two and half fold more oxygen radical absorbance capacity than trolox, due to the phenolic hydroxyl group [26] .…”
Section: Resultsmentioning
confidence: 99%